2019
DOI: 10.1021/acssuschemeng.9b01288
|View full text |Cite
|
Sign up to set email alerts
|

Novel Straw-Derived Carbon Materials for Electromagnetic Interference Shielding: A Waste-to-Wealth and Sustainable Initiative

Abstract: Biomass resources are growing in concern in electromagnetic interference (EMI) shielding due to the advantages of low-cost, sustainability, and unique structural feature. From the perspective of “waste to wealth” and sustainable development, novel straw-derived hollow porous carbon-tube arrays (SCAs) have been fabricated through direct carbonization of wheat straw followed by orderly assembly for the first time. The resultant SCAs with increased SC diameter of ∼1.7–3.3 mm showed not only low apparent density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 43 publications
0
34
0
1
Order By: Relevance
“…The results showed that the EMI SE T of ALC/PDMS EMI shielding composites reached 51 dB with the thickness of 10 mm. Ma et al [ 25 ] obtained straw-derived carbon (SC) aerogel by carbonizing wheat straw at 1500 °C and then prepared SC/epoxy EMI shielding composites by backfilling with epoxy resin. The results showed that the EMI SE T of SC/epoxy EMI shielding composites reached 58 dB with the thickness of 3.3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the EMI SE T of ALC/PDMS EMI shielding composites reached 51 dB with the thickness of 10 mm. Ma et al [ 25 ] obtained straw-derived carbon (SC) aerogel by carbonizing wheat straw at 1500 °C and then prepared SC/epoxy EMI shielding composites by backfilling with epoxy resin. The results showed that the EMI SE T of SC/epoxy EMI shielding composites reached 58 dB with the thickness of 3.3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…However, most carbon-based porous materials are internally crosslinked by weak hydrogen bonds and have poor mechanical properties. Crosslinking through strong chemical bonds generally uses a variety of chemicals, and often produces a large amount of waste liquid, which is very unfriendly to the environment [24].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of highly integrated electronic communications technology and personal electronic equipment, especially for the gradual application of fifth generation wireless system and the proposal of sixth generation of wireless system, electromagnetic interference (EMI) pollution has become a serious pollution, which inevitably disturbs the normal operation of adjacent electronic devices and imposes adverse impacts on human health. [ 1–5 ] Hence, extensive efforts are being made to fabricate EMI shielding materials that effectively address these negative influences. Traditionally, metal‐based composites with high electrical conductivity were widely used to mitigate the transmission of electromagnetic waves (EMW) efficiently, but limited by their disadvantages, such as easy‐corrosion, poor flexibility, manufacturing challenges and serious secondary EMI pollution.…”
Section: Introductionmentioning
confidence: 99%